Metastasis of Uterine Leiomyosarcoma to the Breast: Medical and Histopathological Criteria - Eugenia Colón (Case Reports in Pathology)
It is uncommon for extramammary tumors to metastasize to the breast, and very few cases describing metastasis of primary uterine leiomyosarcoma to the breast have been reported. We present the case of a 51-year-old woman diagnosed with metastasis of uterine leiomyosarcoma to the breast diagnosed 10 years ago after hysterectomy. Ultrasonography, mammography, and cytology were used to establish a preliminary diagnosis that was confirmed upon examination of the excised tumor that show a rare soft tissue tumor composed of atypical spindle cells and increased proliferation rate. We discuss the importance of distinguishing between various primary mesenchymal tumors of the breast because of phenotypic overlap and some guidance of the histological criteria for metastasis of leiomyosarcoma, as well as differential diagnosis and surgical treatment.